Single site video assisted thoracoscopic wedge resection for spontaneous pneumothorax in a pediatric patient - Timothy M. Won; Amanda Muñoz; Marla A. Sacks; Yomara S. Mendez; Laura Goodman; Faraz A. Khan; Andrei Radulescu (Elsevier, 2020)
Surgical treatment for pediatric spontaneous pneumothorax has evolved over time from open thoracotomy to multiport Video Assisted Thoracoscopic Surgery (VATS) and perhaps now towards single site VATS. This is a case of a 16 year-old male with a one-week history of right upper back pain who was found to have a large right-sided spontaneous pneumothorax. Conservative management was attempted, but failed, and he was scheduled for right apical lung blebectomy and mechanical pleurodesis. The decision was made to use a single site approach to minimize sequelae of the surgery. Surgery was successful and the patient was discharged on postoperative day six after a minor air leak subsided. We present this case as evidence for technical feasibility as well as improved postsurgical outcome of single site VATS.